2017
DOI: 10.15288/jsad.2017.78.49
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Offspring Resemblance for Drinking Behaviors in a Longitudinal Twin Sample

Abstract: ABSTRACT. Objective:The purpose of the current study was to evaluate parent-offspring resemblance for alcohol consumption and dependence symptoms, including sex-specific effects, and how these patterns change across adolescence and early adulthood. Method: Three cohorts of twins were assessed longitudinally at five time points between ages 14 and 29 years, with parents directly assessed at intake, using structured interviews. Twin offspring and parents from the population-based Minnesota Twin Family Study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These findings are inconsistent with the research that did not find any significant effects of parental or offspring sex [1, 12, 20, 21]. It is possible that part of the explanation for these inconsistencies is due to differences in the outcomes examined, as Belliveau & Stoppard (1995) examined internalizing symptoms.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These findings are inconsistent with the research that did not find any significant effects of parental or offspring sex [1, 12, 20, 21]. It is possible that part of the explanation for these inconsistencies is due to differences in the outcomes examined, as Belliveau & Stoppard (1995) examined internalizing symptoms.…”
Section: Discussionmentioning
confidence: 60%
“…While Pollock and colleagues [17] showed that daughters of mothers with AUD had elevated rates of AUD themselves, two other reports showed evidence for opposite-sex transmission of problems [18, 19]. Finally, at least four studies did not find significant effects of parental or offspring sex when examining internalizing symptoms, general maladjustment, alcohol use, and alcohol problems [1, 12, 20, 21]. Thus, the question of whether maternal vs. paternal AUD differentially affects sons vs. daughters remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At each assessment, individuals reported on lifetime and past 12-month substance use using a computerized substance use inventory (McGue et al ., 2014; Saunders et al ., 2017) administered in a private room. Age-11 and age-14 measures were aggregated to measure cumulative use/initiation by age-14.…”
Section: Methodsmentioning
confidence: 99%
“…Within the family environment, parental modeling of alcohol use is also a strong predictor of their offspring's alcohol use during both adolescence (Alati et al, 2014; Latendresse et al, 2008) and emerging adulthood (Casswell et al, 2002; Merline et al, 2008; Saunders et al, 2016). Notwithstanding the dramatic increased rates of alcohol use cited above (Grant et al, 2017), African American youth, on average, may be more likely to be exposed to abstinence models and norms than their non-African American peers (Zapolski et al, 2014).…”
Section: Role Of Parents In Predicting Emerging Adults' Alcohol Usementioning
confidence: 99%